2019
DOI: 10.1186/s40104-019-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

Meclofenamic acid represses spermatogonial proliferation through modulating m6A RNA modification

Abstract: Background N6-Methyladenosine (m 6 A), the most prevalent modification in mammalian mRNA, plays important roles in numerous biological processes. Several m 6 A associated proteins such as methyltransferase like 3 (METTL3), methyltransferase like 14 (METTL14), α-ketoglutarate-dependent dioxygenase AlkB homolog 5 (ALKBH5) and YTH domain containing 2 (YTHDC2) are involved in the regulation of spermatogenesis and oogenesis. However, the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“… ALKBH5 Pre-mRNA splicing Spermatocytes and round spermatids Controls splicing and stability of long 3′-UTR mRNAs in male germ cells 142 . FTO mRNA decay Hela cells Inhibited by MA2 is accompanied with elevated m6A levels in cyclin-dependent kinases, accelerating their destabilization and impairing the cell cycle progression 143 . YTHDC2 mRNA decay Spermatogonia Facilitates a clean switch from mitosis to meiosis in mouse germ cells by downregulating genes expression that are important for mitosis 144 147 .…”
Section: A and Normal Physiological Behaviorsmentioning
confidence: 99%
“… ALKBH5 Pre-mRNA splicing Spermatocytes and round spermatids Controls splicing and stability of long 3′-UTR mRNAs in male germ cells 142 . FTO mRNA decay Hela cells Inhibited by MA2 is accompanied with elevated m6A levels in cyclin-dependent kinases, accelerating their destabilization and impairing the cell cycle progression 143 . YTHDC2 mRNA decay Spermatogonia Facilitates a clean switch from mitosis to meiosis in mouse germ cells by downregulating genes expression that are important for mitosis 144 147 .…”
Section: A and Normal Physiological Behaviorsmentioning
confidence: 99%
“…Unlike other regulatory factors, the expression of FTO increased by VCD and then decreased after HYYKF treatment, which may not be consistent with other studies. One study has reported that after inhibiting the activity of FTO, the proliferation of mouse spermatogonia cells was decreased (Huang et al, 2019). In addition, a case-controlled study showed that the FTO protein expression level was significantly lower in POI patients than in normal people (Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting ALKBH5 results in aberrant splicing and shorter transcripts of mRNAs, ultimately developing meiosis abnormity of spermatocytes and male infertility in mice [77,78]. Meclofenamic acid suppresses cell viability and blocks G1/S progression in spermatogonia of mice through accelerating the degradation of CDK2 mRNA via specifically decreasing FTO and elevating the m 6 A content of 3'UTR [79].…”
Section: A In Adipogenesis and Obesitymentioning
confidence: 99%